Nowcasting Brazilian GDP - Mattos, Pedro Montero (2017)
Based on recent surveys on nowcasting methods, we apply the one-step estimation of dynamic factor models to the Brazilian case. Such methodology copes well with the problems of mixed-frequency series, ragged edges, timeliness and high dimensionality of data sets. We use the daily expectation published by the Brazilian Central Bank as a benchmark for our model and we do not ﬁnd enough evidence to reject that both models have equal predictive accuracy, under non-distressed circumstances.